Accessing Digital Divide and Implications in Nigeria: The Media Dimension - Vitalis, Perpetua Ogechi; Aondover, Eric Msughter; Ogunbola, Omotola; Onyejelem, Timothy Ekeledirichukwu; Ridwan, Muhammad (Budapest International Research and Critics University, 2025)
The digital divide connotes the gap between those who have access to modern information and communication technologies (ICT) and those who do not, due to various factors like income, education, geographic location, or infrastructure. In the context of Nigeria, this divide has profound implications for economic, social, and political development, particularly in the realm of media. The media dimension of the digital divide explores the unequal access to digital platforms, content, and technologies, which influences the dissemination of information, civic engagement, and media consumption. The postulation of Diffusion of Innovation Theory was employed to achieve the goal of this paper. The paper argues that digital literacy, which includes the ability to use digital devices and navigate online platforms, is still a challenge in Nigeria. Although there has been a surge in mobile phone ownership, a large portion of the population, particularly older generations and those in remote areas, lack the necessary skills to fully benefit from digital media platforms. This lack of digital literacy hampers the capacity of citizens to engage with online news, education, and government services. The paper concludes that the digital divide in Nigeria, particularly in the media dimension, has significant implications for access to information, political participation, social inclusion, and education. While efforts to bridge this divide are underway, much work remains to be done. By addressing the infrastructure, economic, and digital literacy challenges, Nigeria can begin to close the digital divide and ensure that all its citizens can participate fully in the digital age.